(untitled) (Environment & Health, 2021)
Objective: We presented a comprehensive description of the changes in the health status of the adult population of radioactively contaminated territories of Ukraine depending on gender and age at the date of the Chornobyl accident on the basis of cohort epidemiological studies after accident. Materials and methods: The epidemiological analysis of non-neoplastic morbidity, disability, mortality in the residents of radioactively contaminated territories (RCT) aged 18-60 years old at the date of the Chornobyl accident (65,189 people) was conducting during 1988-2016 for five-year observation periods and by eight classes of ICD-10. We applied the methods of mathematical and statistical analysis. Results: During 1988-2016, 90590 (100%) cases of non-neoplastic morbidity (34.94% in men and 65.06% in women), 11153 (100%) cases of disability (38.22% and61.78%, respectively), and 11586 (100%) cases of mortality(50,42% and 49,58%, respectively)were detected in the residents of the RCT for the first time as a result of epidemiological study. Most of the victims suffered from the nosological forms of the nosological forms of respiratory, circulatory and digestive systems, which made up 67.43% in the structure of non-neoplastic morbidity. Diseases of circulatory, endocrine and nervous systems (87.92%) were the main factors of disability and diseases of circulatory system (89.49%) - of mortality. The gender dependence of the development of the incidence of non-neoplastic diseases, disability and mortality due to them were established. The indices of mortality (116.08, ID/103 man-years of observation) and disability (13.57)in females significantly exceeded the males’ ones (86.57 and 11.65, respectively). But males had a higher mortality rate (16.01 vs. - 11.32). Changes in the incidence rates of non-neoplastic diseases, disability and mortality due to them throughout the observation period were characterized by a divergence of vectors: morbidity decreased, and disability and mortality increased simultaneously. The intersection of the dynamics of the mortality of non-neoplastic diseases with disability and mortality through those diseases was identified in 2008-2012. Conclusions 1. During epidemiological surveillance in 1988-2016, in the residents of RCT aged 18-60 years old on the date of the Chornobyl accident epidemiological surveillance, the non-neoplastic morbidity was formed mainly due to the significant development of diseases of the respiratory, circulatory and digestive systems, which together made up 67.43%. Non-neoplastic diseases of the circulatory, endocrine and nervous systems (87.92) were the main causes of disability, diseases of circulatory system (89.49%) - of mortality. 2. The gender dependence of the development of the morbidity of non-neoplastic diseases, disability and mortality in the residents of RCT over the thirty-year observation period was established. Diseases of the circulatory system were the main causes of disability and mortality. In males, disability and mortality were caused by the mental and behavioral disorders, diseases of respiratory and digestive systems, in females - by the diseases of nervous and urogenital systems. 3. In the residents of RCT, regardless of gender, over the years of observation, a feature of the development of morbidity, disability and mortality due to them was established, it was in the significant reduction of the incidence of diseases in 2008-2016, due to the increase of disability and mortality of the suffered, especially in 2008-2016, in comparison with the previous years, i.e. in 22-30 years after the Chornobyl accident. 4. Summarizing the obtained data, it is important to continue the epidemiological studies of the health status of the residents of RCT (non-neoplastic morbidity, disability, mortality) for the determination of the impact of radiation on the development of the main forms of non-neoplastic diseases.